Pengaruh Etos Kerja, Lingkungan Kerja dan Beban Kerja terhadap Kepuasan Kerja Pegawai Puskesmas Balai Selasa Kabupaten Pesisir Selatan - Noza Apria Aulya Putri; Zusmawati Zusmawati (Lembaga Yasin AlSys, 2026)
Although job satisfaction has been widely studied, research that specifically examines the influence of work ethic, work environment, and workload in health service institutions remains limited. This study aims to analyze the influence of work ethic, work environment, and workload on employee job satisfaction at Balai Selasa Community Health Center. This study used a quantitative approach with a survey design, involving 78 respondents selected using total sampling. Data were collected using a questionnaire and analyzed through multiple linear regression with the assistance of SPSS. The results showed that work ethic, work environment, and workload had a positive and significant effect on employee job satisfaction. These findings contribute to the development of human resource management studies and expand understanding of the factors that influence job satisfaction in the health service sector. The conclusion of this study confirms that strengthening work ethic, creating a conducive work environment, and managing workload properly are important aspects in improving employee job satisfaction at Balai Selasa Community Health Center.